Clinical Efficacy and Safety of the Intra-articular Injection of Autologous Adipose-Derived Mesenchymal Stem Cells for Knee Osteoarthritis: A Phase III, Randomized, Double-Blind, Placebo-Controlled Trial - Kim, Kang-Il; Lee, Myung Chul; Lee, Ju Hong; Moon, Young-Wan; Lee, Woo-Suk; Lee, Han-Jun; Hwang, Sun-Chul; In, Yong; Shon, Oog-Jin; Bae, Ki-Cheor; Song, Sang-Jun; Park, Kwan Kyu; et al. (The American journal of sports medicine, 2023)
Intra-articular injection of autologous culture-expanded adipose-derived mesenchymal stem cells (ADMSCs) has introduced a promising treatment option for knee osteoarthritis. Although the clinical efficacy and safety of ADMSCs have been reported, the treatment remains controversial owing to the small sample sizes and heterogeneous osteoarthritis grades in previous studies. To assess the efficacy and safety of intra-articular injection of ADMSCs as compared with placebo in alleviating pain and improving functional capacity in a large sample of patients with knee osteoarthritis of Kellgren-Lawrence (K-L) grade 3. Randomized controlled trial; Level of evidence, 1. This phase III multicenter clinical trial was a double-blind randomized controlled study that included 261 patients with K-L grade 3 symptomatic knee osteoarthritis who were administered a single injection of autologous culture-expanded ADMSCs or placebo. Clinical data were assessed at baseline and at 3 and 6 months after the injection. The primary endpoints were improvements in 100-mm visual analog scale (VAS) for pain and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for function at 6 months after the injection. The secondary endpoints included clinical and radiologic examinations and safety after injection. The changes in cartilage defects after injection were assessed by magnetic resonance imaging at 6 months. The ADMSC and control groups included 125 and 127 patients available for follow-up, respectively. At 6 months, the ADMSC group showed significantly better improvements in 100-mm VAS (ADMSC vs control, 25.2 vs 15.5; = .004) and total WOMAC score (21.7 vs 14.3; = .002) as compared with the control group. The linear mixed model analysis indicated significantly better improvements in all clinical outcomes in the ADMSC group after 6 months. At 6 months, the ADMSC group achieved significantly higher proportions of patients above the minimal clinically important difference in 100-mm VAS and WOMAC score. Radiologic outcomes and adverse events did not demonstrate significant differences between the groups. No serious treatment-related adverse events were observed. Magnetic resonance imaging revealed no significant difference in change of cartilage defects between the groups at 6 months. Intra-articular injection of autologous culture-expanded ADMSCs provided significant pain relief and functional improvements in patients with K-L grade 3 osteoarthritis. Long-term results are needed to determine the disease-modifying effects of ADMSCs, such as structural changes, and the duration of effect of intra-articular injection of ADMSCs in knee osteoarthritis. NCT03990805 (ClinicalTrials.gov identifier).